2022
DOI: 10.1097/md.0000000000029233
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of embryo vitrification at different developmental stages

Abstract: Introduction: Advances in cell culture media have led to a shift from cleavage stage embryo transfer to blastocyst stage transfer. Extended embryo culture to the blastocyst stage provides some theoretical advantages and disadvantages. There has been controversy. This study is sought to evaluate the clinical outcomes of vitrified-warmed cleavage-stage and blastocyst-stage embryo transfers in patients undergoing Artificial Reproductive Technique treatments.Material and method: The study was performed on 2740 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Blastocysts are preimplantation embryos that successfully pass the critical step of genomic activation and have a high developmental potential [12,18]. Furthermore, blastocyst transfer is more physiologically appropriate because it is closer to the time of natural implantation and may improve the synchronization of the endometrium and embryo development [18,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blastocysts are preimplantation embryos that successfully pass the critical step of genomic activation and have a high developmental potential [12,18]. Furthermore, blastocyst transfer is more physiologically appropriate because it is closer to the time of natural implantation and may improve the synchronization of the endometrium and embryo development [18,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…With gradual developments in technology and preimplantation embryo culture, the number of blastocyst transfers has continuously increased [13]. Many studies have demonstrated the theoretical advantages of blastocyst transplantation, indicating a better correlation between morphology and aneuploidy, better synchronization with endometrium, and increased implantation potential [12,13,17,18]. Blastocyst transfer has become more common globally; however, selecting the best embryos from blastocysts is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Vitrification protocols have also been improved, and usually a mixture of ethylene glycol and dimethyl sulfoxide is applied as a cryoprotectant, in association with an extracellular cryoprotectant, such as sucrose. 48 Choosing the cryopreservation method is crucial because the ability of the embryo to survive reflects in the implantation ability. Commonly, to perform the transfer after the cryopreserved embryo is thawed/warmed, patients showing a natural ovulatory cycle do not need further hormonal manipulation.…”
Section: Current Feasible Alternatives Formentioning
confidence: 99%
“…49,50 In addition, patients with a thin endometrial wall, or other complications, such as prolonged menstruation and bleeding at ovulation are offered a treatment with ethinyl and/or progesterone. 48 For the transfer, embryos are deposited in the uterus through a catheter, in the lower to mid portion. 51 Analgesia or anesthesia is not mandatory for performing transcervical embryo transfer.…”
Section: Current Feasible Alternatives Formentioning
confidence: 99%